A novel mathematical model for analysis of the cracked planet gear. (August 2022) - Ouyang, Tiancheng; Wang, Geng; Yang, Rui; Mo, Xiaoyu
Highlights: An improved method for mesh stiffness of planetary gear set with crack is proposed. Influences of crack size and inclination angle on mesh stiffness are investigated. Effect of crack level on vibration response in time and frequency domains is studied. Statistical indicators are used to characterize the evolution of crack propagation. Abstract: The crack fault often appears in the complicated gear system, and even causes tooth broken. To solve this problem, an improved model is proposed in this paper, which considers the coupling effect of cracks on both gear tooth and gear foundation, and a 2D finite element model is established to verify the proposed method. The influences of crack size and inclination angle on meshing stiffness are investigated. The results are used to simulate the situation of the crack occurring at the sun gear in an 18 degrees of freedom dynamic model of the planetary gear set, so as to obtain the dynamic responses of the crack gear system both in time domain and frequency domain. Finally, two different methods are used to process the original vibration signals to obtain the residual signals. Combining the residual signals, several statistical indicators are employed to characterize the evolution of crack propagation.